Fire fighting pumping systems at industrial facilities - Nolan, Dennis P. (Gulf Professional Publishing, an imprint of Elsevier, 2017)
Fire Pump Arrangements at Industrial Facilities, Third Edition delivers a practical reference from an author with a successful professional career in fire protection and loss prevention engineering in the oil and gas industry. While most regulatory standards are left to interpretation and try to cover multiple industries in one location, this book focuses on the equipment, standards and operations specific to the petroleum industry, covering quality controls, pump drivers and scheduled maintenance and audits so the equipment remains in safety compliance. Enhanced with new sections on human factors, case studies for modeling fire accidents and a look at recent events that have further shaped the safety and testing of fire pumps, the book provides the engineer and manager with a critical oil and gas resource for every aspect of firewater pumps. Remains the go-to reference for loss prevention specialists and fire engineering specific to the oil and gas industryEnhanced with new sections on quality audits and new case studies that evaluate operational issues and applicationsFills in the practical hands-on information gap not covered in the regulatory standards.
Keywords: Industrial buildings -- Fires and fire prevention -- Equipment and supplies.; Fire pumps.; elektronické knihy; electronic books